Pendeteksian Markerless Pada Aplikasi Augmented Reality (AR) Tuntunan Shalat Sesuai Mazhab Syafi’i Menggunakan Algoritma FAST - Adriadi Karya Anugerah; Youllia Indrawaty Nurhasanah; Rio Korio Utoro (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
Praying is a pillar of Islam based on the law that is divided into two kinds namely Mandatory and Sunnah. People usually are not aware of how to perform prayers properly and correctly, because prayer education is still given conventional only using the book as a guide. Therefore it is a necessary alternative learning media using augmented reality technology which is applied to mobile android, so users can learn the guidance of prayer anywhere and anytime. The application that was built in this research is based on interactive multimedia using augmented reality technology, where the user not only read and view the picture but they can also see the motion animation along with the sound of the movement prayer. The user also can notice the whole movement of prayers from all sides, both from the front, side or the back. Testing was conducted on 20 respondents with age criteria of 10 until 40 years. The result shows 80% respondents that had tried the application agree that the application has an attractive appearance, for the information presented is clear, and it is easy to use and responsive. The conclusion shows that the application is feasible to use.